Play Montage to Improve The Intelligence of The Early Children's Language - Rachma, Septia Faulla (Early Childhood Research Journal (ECRJ), 2019)
Review Literature: Play MontageÂ  To Improve The Intelligence Of The Early Children's Language. Playing montage is an early childhood activity that produces a work consisting of several pieces of picture forming a unity of images in one field. The author aims to review the literature review, articles, and research documents that refer to the activity of montage early childhood and language intelligence stimulation in early childhood. This research method is searching scientific articles from the database using the word montage and children's language development in the last 5 years and the last 7 years, the search results obtained 20 articles consisting of 15 national journals for the past 5 years and 5 international journals for a period of time Last 7 years. In the results and discussion that the literature review shows montage activity can find ideas to apply various kinds of images to formwork, children's language skills can be stimulated through the method of telling stories using images in accordance with the imagination of each child. The results show that montage journals that have a positive influence have a percentage of 30% and children's language intelligence journals that have a positive effect have a percentage of 65%. This literature review can be concluded that playing montage is one way to improve a child's new vocabulary by means of a cut of a child's image producing a montage work and the child is able to tell work, this helps the child in stimulating language intelligence in early childhood.Keywords: Play montage, Children's intelligence, children's language